2017
DOI: 10.1038/cddis.2017.410
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of fibroblast growth factor 21 against doxorubicin-induced toxicity via the SIRT1/LKB1/AMPK pathway

Abstract: Doxorubicin (DOX) is a highly effective antineoplastic anthracycline drug; however, the adverse effect of the cardiotoxicity has limited its widespread application. Fibroblast growth factor 21 (FGF21), as a well-known regulator of glucose and lipid metabolism, was recently shown to exert cardioprotective effects. The aim of this study was to investigate the possible protective effects of FGF21 against DOX-induced cardiomyopathy. We preliminarily established DOX-induced cardiotoxicity models in H9c2 cells, adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 47 publications
2
112
1
Order By: Relevance
“…It is noteworthy that the LKB1/AMPK/Sirt1 axis and its downstream targets are highly sensitive targets for DOX‐induced cardiac injury . SIRT1 is reported to have a critical role in controlling the cardiac LKB1/AMPK pathway . Activated Sirt1 can also regulate the activity of the peroxisome proliferator‐activated receptor gamma coactivator 1 alpha (PGC‐1α) and further up‐regulate its expression .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the LKB1/AMPK/Sirt1 axis and its downstream targets are highly sensitive targets for DOX‐induced cardiac injury . SIRT1 is reported to have a critical role in controlling the cardiac LKB1/AMPK pathway . Activated Sirt1 can also regulate the activity of the peroxisome proliferator‐activated receptor gamma coactivator 1 alpha (PGC‐1α) and further up‐regulate its expression .…”
Section: Discussionmentioning
confidence: 99%
“…FGF21, a hormone‐like member of the FGF family, is induced by endoplasmic reticulum (ER) stress, mitochondrial dysfunction, and autophagy (Suwa et al, ). FGF21 controls energy metabolism by enhancing energy expenditure, ameliorates age‐related metabolic disorders such as atherosclerosis, obesity, and T2DM (Suwa et al, ), upregulates hepatic PGC‐1α expression (Potthoff et al, ), increases NAD levels leading to the activation of SIRT1 and the deacetylation of PGC‐1α that consequently activates PGC‐1α in adipocytes (Chau, Gao, Yang, Wu, & Gromada, ), and enhances SIRT1 binding to liver kinase B (LKB1), which decreases LKB1 acetylation and subsequently induces the activation of AMPK in cardiomyocytes (Wang, Wang, Zhang, Liu, & Gu, ). The transgenic overexpression of FGF21 extends the lifespan of mice by blunting the growth hormone/insulin‐like growth factor 1 signaling pathway in the liver (Zhang et al, ).…”
Section: Pgc‐1α: a Key Player In Metabolismmentioning
confidence: 99%
“…In favour of these findings, it has been demonstrated that dunnione, a natural quinone with extensive structural analogies to B-LAP, elevates nuclear presence of Nrf2 and simultaneously up-regulates the expressions of HO-1 and NQO1 in the kidneys of cisplatin nephrotoxic rats. 28 Additionally, Wang et al 29 showed that the activation of SIRT/LKB1/AMPK signalling pathway protects H9c2 cells, adult mice cardiomyocytes and 129S1/ SyImJ mice against DOX-induced cardiotoxicity through anti-oxidative, anti-apoptotic and anti-inflammatory actions. Moreover, it was reported that DOX-induced cardiotoxicity can be reversed by activation of Sirt1/AMPK/Nrf2 pathway by suppression of intracellular oxidative stress.…”
Section: Discussionmentioning
confidence: 99%